Zur Frage über die Anzahl der unzerfällbaren Darstellungen der Z8 - Matuliauskas, A. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Матуляускас. К вопросу о числе неразложимых представлений группы Z8 A. Matuliauskas. Grupės Z8 neišskaidomų atvaizdavimų skaičiaus klausimu